Effect of surface treatments on the bond strength of a resin cement to commercially pure titanium - de Almeida-Júnior, Antonio Alves [UNESP]; Fonseca, Renata Garcia [UNESP]; Haneda, Isabella Gagliardi [UNESP]; Abi-Rached, Filipe de Oliveira [UNESP]; Adabo, Gelson Luis [UNESP] (FapUNIFESP (SciELO), 2010)
Investigation of the effectiveness of surface treatments that promote a strong bond strength of resin cements to metals can contribute significantly to the longevity of metal-ceramic restorations. This study evaluated the effect of surface treatments on the shear bond strength (SBS) of a resin cement to commercially pure titanium (CP Ti). Ninety cast CP Ti discs were divided into 3 groups (n=30), which received one of the following airborne-particle abrasion conditions: (1) 50 μm Al2O3 particles; (2) 30 μm silica-modified Al2O3 particles (Cojet Sand); (3) 110 μm silica-modified Al2O3 particles (Rocatec). For each airborne-particle abrasion condition, the following post-airborne-particle abrasion treatments were used (n=10): (1) none; (2) adhesive Adper Single Bond 2; (3) silane RelyX Ceramic Primer. RelyX ARC resin cement was bonded to CP Ti surfaces. All specimens were thermally cycled before being tested in shear mode. Failure mode was determined. The best association was Rocatec plus silane. All groups showed 100% adhesive failure. There were combinations that promote higher SBS than the protocol recommended by the manufacturer of RelyX ARC.
Keywords: Airborne-particle abrasion; Resin cement; Silica coating; Surface treatment; Titanium; resin cement; titanium; analysis of variance; chemistry; dental bonding; dental care; dental debonding; dental surgery; human; mechanical stress; methodology; nonparametric test; particle size; shear strength; surface property; Air Abrasion, Dental; Analysis of Variance; Dental Bonding; Dental Debonding; Dental Restoration Failure; Dental Restoration, Permanent; Dental Stress Analysis; Humans; Particle Size; Resin Cements; Shear Strength; Statistics, Nonparametric; Stress, Mechanical; Surface Properties